Un ticket pour la liberté - Nabil Mouline (Revue des Mondes Musulmans et de la Méditerranée, 2013)
For various reasons, the Egyptian film industry has gone through dramatic changes in the early 2000s. One tangible consequence of such changes was the production –whether or not intentional - of protest films that objected to prevailing viewpoints and sought to break the taboo on several socio-political issues. Not only did these films serve as historical documents reflecting the state of society, but they also proved efficient as tools of soft influence and mobilization and contributed to the creation of an imagined community, part of whom took to the streets on January 25, 2011. Based on the analysis of a large sample of blockbuster films, our article sheds light on the dual role played by Egyptian cinema between 2001 and 2010.